Characterization of the complete chloroplast genome of Aconitum flavum (Ranunculaceae) - Yi Liu; Shuhua Yu; Fengming You (Mitochondrial DNA. Part B. Resources, 2020)
Aconitum flavum, a traditional Chinese medicine. The complete chloroplast genome sequence is 155,654 bp in length, with one large single copy region of 86,390 bp, one small single copy region of 16,968 bp, and two inverted repeat (IR) regions of 26,148 bp. It contains 129 genes, including 83 protein-coding genes, 8 ribosomal RNA, and 37 transfer RNA. Phylogenetic tree shows that this species is a sister to A. brachypodum.